A Reconstruction of the Business Judgment Rule Doctrine from the Perspective of Modern Civil Law: Between Director Protection and Corporate Accountability - Selamat Lumban Gaol; Mawardi Mawardi; Abdulwahab Abdullah Al-Maamari (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
The business judgment rule (BJR) is a fundamental doctrine in corporate law that provides legal protection to directors for business decisions made in the course of managing a company. Such protection applies as long as the decisions are taken in good faith, with due care, and within the scope of their lawful authority. In practice, this doctrine functions to prevent excessive interference in business policies, which inherently involve risk and uncertainty. However, along with the development of modern civil law, which increasingly emphasizes the principles of justice, transparency, and accountability, the BJR doctrine requires conceptual reconstruction to prevent its misuse as a shield against legal responsibility. This study aims to examine the concept of the BJR within the framework of Indonesian positive law and to formulate a reconstruction model that is more responsive to the dynamics of modern civil law. The research employs a normative juridical method with statutory and conceptual approaches. The analysis is conducted through a review of primary and secondary legal sources related to directors’ liability and the duty of care in corporate governance. The findings indicate that the regulation of the BJR in Indonesia still contains normative ambiguities, particularly concerning the parameters of good faith and the standards of due care, which have not been clearly and objectively defined. The novelty of this study lies in proposing a reconstruction model of the business judgment rule based on objective parameters for assessing good faith and due care. This study contributes a normative framework to strengthen legal protection for directors while reinforcing the principle of corporate accountability. Therefore, a reconstruction of the BJR doctrine is necessary through the strengthening of objective parameters, enhancement of transparency in decision-making processes, and reinforcement of corporate accountability principles in order to achieve a balance between the protection of directors and legal responsibility.